2015
DOI: 10.1515/chem-2015-0142
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of polyphenolic compounds in Ilex Sp.

Abstract: Qualitative and quantitative analysis of polyphenolic compounds in Ilex Sp. DOI: 10.1515/chem-2015-0142 received February 15, 2015 accepted October 1, 2015. Abstract: Natural compounds are an important source of desired biological activity which help to improve nutritional status, enhance productivity and bring many health benefits. The leaves of the Ilex paraguariensis (Aquifoliaceae) are used for preparing a beverage known as yerba mate and represent a proven source of natural polyphenols which are known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Our preliminary study [ 12 ] confirmed that Ilex species other than I. paraguariensis also contain a high amount of polyphenolic fraction (rich in rutin, quinic acid, and its caffeoyl esters), triterpenes, as well as their glycosides (saponins). The similarity of phytoconstituents in European Ilex × meserveae S. Y. Hu “Blue Angel” and South American I. paraguariensis allows us to consider I. meserveae “Blue Angel” as a promising source of bioactive compounds [ 12 ]. Of the above, caffeoylquinic esters were generally found to be interesting remedies for lowering blood cholesterol [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our preliminary study [ 12 ] confirmed that Ilex species other than I. paraguariensis also contain a high amount of polyphenolic fraction (rich in rutin, quinic acid, and its caffeoyl esters), triterpenes, as well as their glycosides (saponins). The similarity of phytoconstituents in European Ilex × meserveae S. Y. Hu “Blue Angel” and South American I. paraguariensis allows us to consider I. meserveae “Blue Angel” as a promising source of bioactive compounds [ 12 ]. Of the above, caffeoylquinic esters were generally found to be interesting remedies for lowering blood cholesterol [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 64%
“…Extracts from I. meserveae dried leaves were prepared with 80% methanol as the solvent, according to the method presented by Zwyrzykowska et al [ 12 ]. The resulting fine powder was sufficiently soluble in water at experimental concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the highest level of phenolic compounds was found in the leaf extract [ 15 ]. From chromatographic analyses, the TPC was determined as about 51 mg/g dry mass (DM) in I. paraguariensis [ 41 ]. Moreover, determination of the TPC in Yerba Mate was performed by the Folin-Ciocalteu method, where 111 samples from the Parana State in Brazil were characterized [ 18 ].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…I. paraguariensis, as a natural antioxidant, effectively reduced the oxidative changes in lipid fraction of hamburgers [11] and fermented Italian-type sausages [12] and chicken meat balls [13]. Ilex meserveae "Blue Angel" is characterized by a higher content of some polyphenols (e.g., chlorogenic acid and rutin) than I. paraguariensis [14], although information on the possibilities of its use in food processing is lacking. Hence, the authors used it in the dry-aging of beef.…”
Section: Introductionmentioning
confidence: 99%